“Just the Flu” in 1323? The Case study of a Highly Contagious Epidemic with Low Mortality and Its Possible Origins in Late Medieval Europe - Bauch, Martin (Journal for the History of Environment and Society, 2020)
Abstract This contribution investigates the possibilities of identifying Covid-19-like, highly infectious epidemics with low mortality rates in the premodern era. In its discussion of the chances and limits of such an endeavour, the essay focuses on a case study from 1323, when an epidemic that caused high fevers but relatively few deaths affected large parts of Europe, including Italy. The indications available in the historical records are examined in light of criteria that have been developed from modern influenza pandemics research. Finally, the essay examines the possible zoonotic origins of the 1323 epidemic and proposes broader lessons that could be drawn from researching premodern pandemics.